Predictors of Success in the Treatment of Obstructive Sleep Apnea Syndrome with Mandibular Repositioning Appliance: A Systematic Review - Saffer,Fernanda (2015)
Introduction Obstructive sleep apnea syndrome affects up to 4% of middle-aged men and 2% of adult women. It is associated with obesity. Objective The objective of this article is to review the literature to determine which factors best correlate with treatment success in patients with obstructive sleep apnea syndrome treated with a mandibular repositioning appliance. Data Synthesis A search was performed of the PubMed, Cochrane, Lilacs, Scielo, and Web of Science databases of articles published from January 1988 to January 2012. Two review authors independently collected data and assessed trial quality. Sixty-nine articles were selected from PubMed and 1 from Cochrane library. Of these, 42 were excluded based on the title and abstract, and 27 were retrieved for complete reading. A total of 13 articles and 1 systematic review were considered eligible for further review and inclusion in this study: 6 studies evaluated anthropomorphic and physiologic factors, 3 articles addressed cephalometric and anatomic factors, and 4 studies evaluated variables related to mandibular repositioning appliance design and activation. All the studies evaluated had low to moderate methodologic quality and were not able to support evidence on prediction of treatment success. Conclusion Based on this systematic review on obstructive sleep apnea syndrome treatment, it remains unclear which predictive factors can be used with confidence to select patients suitable for treatment with a mandibular repositioning appliance.